Searching combinatorial chemistry: from biochips to catalysts and beyond––an EPO perspective - Stevnsborg, Niels (World patent information, 2002)
This article provides an overview of searching in the field of combinatorial chemistry, from a perspective of the European Patent Office. Combinatorial chemistry has for some an aura of mystique surrounding it. This article seeks to demystify this subject and starts with an outline of its raison d'être, some definitions of its main elements, followed by a brief history. Further, data is presented on the publication activity and how documents are handled for search, in particular with reference to classification, including developments in the IPC and in European classification. Some resources of special interest in respect of combinatorial chemistry are listed. Various elements for setting up search strategies relating to combinatorial chemistry are also presented.